Regulating the interfacial reaction pathway by controlling the disproportionation of lithium polysulfides to improve the performance of lithium-sulfur batteries - Lee, Seungmin; Sim, Kiyeon; Cho, Ki-Yeop; Kim, Subin; Eom, Kwangsup (Elsevier BV, 2023)
Lithium-sulfur batteries are promising candidates for next-generation energy storage systems due to their high energy densities and low cost for the cathode compared to commercialized lithium-ion batteries. Nevertheless, the multistep electrochemical reaction between lithium and sulfur involving both solid-phase and liquid-phase intermediates has led to poor sulfur utilization and sluggish electrochemical kinetics, degrading the electrochemical performance. One effective strategy that has been suggested to suppress degradation is modifying the solvents/additives to increase solution-mediated pathways and control the loss of active materials due to disproportionation. Even though these strategies have improved the performance, the attack of modified solvents/additives on Li metal has hindered their practical application. Additionally, the quantitative effectiveness has rarely been studied due to the difficulty in investigating it during electrochemical reaction in real time. In this work, we regulate disproportionation using a sulfur-containing compound with less aggressive towards Li metal as an electrolyte additive and quantitatively evaluate its effect on performance using a real-time electrochemical method. It is found that the sulfur-containing additive improves the utilization of active materials and electrochemical kinetics at the sulfur cathode. This effectiveness of the additive is verified in a sulfur cathode with higher S loading as well.